Comparative Analysis of Waqf Link Governance of Sukuk (CWLS) Money to Finance Infrastructure in the Perspective Studies of Law Number 41 of 2004 and Sharia Economic Law Study - Firdaus, Doddy Afandi; Masngudi, Masngudi (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2023)
Sukuk-waqf is an innovation for economic sustainability, overcoming the humanitarian funding gap, for charitable fundraising or humanitarian purposes, and a modern scheme for developing waqf assets. CWLS is a cash waqf program resulting from collaboration and innovation in Islamic finance and social investment in Indonesia. The existence of CWLS contributes to the development of the Islamic economy in Indonesia. This shows that the capacity of the sharia economy is broad and makes a contribution to national development. The approach in this study uses a Socio-Legal and Hermeneutic approach. In Law 41 of 2004 concerning Waqf related to Financing it is explained in Article 59, namely in carrying out BWI duties, the Government is obliged to assist with operational costs. CWLS is allowed because it is in Law Number 41 of 2004 and clarified by Law number 42 of 2006. In the governance of the implementation of CWLS in Indonesia it has been carried out in accordance with an Islamic economic perspective, it has been proven that the DSN-MUI Fatwa regarding Wakaf Sukuk has been established.